PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI PT SANGHIANG PERKASA BRANCH OFFICE CIREBON - Nur Octavia; Jumriah Basri (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine and explain the influence of work motivation and competency on employee performance at PT Sanghiang Perkasa Branch Office Cirebon. The method used in this study is a quantitative approach. Data were collected by conducting a survey using a questionnaire with a population of 35 employees, data processing analysis using SPSS version 26. The results of the study showed that work motivation had a significant effect on employee performance, this is evidenced by the tcount value > ttable (3.909 > 2.036). Competency has a significant effect on employee performance, this is evidenced by the tcount value > ttable (4.498 > 2.036). Work motivation and competency simultaneously have a significant effect on employee performance, this is evidenced by the Fcount value > Ftable (47.673 > 3.29). The magnitude of the influence of the independent variable on the dependent is 74.9%, while the remaining 25.1% is influenced by other variables not examined in this study. The implications of this study indicate that efforts to improve employee performance can be done effectively through strengthening work motivation and developing competencies on an ongoing basis.